(untitled) (SCIÉNDO INGENIUM, 2022)
The present article "Termination and early conclusion in sexual crimes against the constitutional principle of equality in Peru", has the purpose of determining if the non-applicability of these legal figures in sexual crimes in Peru complies with the constitutional parameters of equality, because by prohibiting the application of these mechanisms they transgress the constitutional principle of equality. Regarding the methodology, it has a qualitative approach; Non-experimental design, the instrument applied is the registration form, whose scenario was 7 sentences of the CSJS of termination and conclusion in the matter of acts against indecentness, and it was concluded that the non-applicability of these procedural institutions in sexual crimes does not comply with the constitutional parameters of the principle of equality, since the results indicate that according to file no. 02 in exp. N°00409-2020-9-2501-JR-PE-05 although the benefit is applied, however, the reduction of the penalty becomes effective.